Offender management in and after prison: The end of 'end to end'?. (April 2017) - Maguire, Mike; Raynor, Peter
In 2013 a joint report by the Inspectorates of Probation and Prisons in England and Wales concluded that offender management in prisons was 'not working' and called for a fundamental review. This article considers why existing arrangements have failed and draws upon theory and research on resettlement, case management and desistance from crime, to define what a more effective system of 'rehabilitative resettlement' – both inside prison and 'through the gate' – might look like. It also comments on emerging proposals for radical change, including abandonment of the 'end to end' model of offender management by an outside probation officer and the development of 'rehabilitative prisons', in which more responsibility is placed on prisoners for managing their own rehabilitation, and a formal motivational role is created for large numbers of prison staff.